Sistem Pendukung Keputusan Menentukan Mitra Berprestasi di Halal Mart Menggunakan Metode AHP – WASPAS - Aprilia, Nia; Zufria, Ilka (AI Society & STMIK Indonesia, 2022)
PT Herbal Penawar Alwahida Indonesia, known as HNI-HPAI, is one of several companies in Indonesia as a Halal Network business that focuses on providing various quality and halal consumer goods products. With the number of partners spread throughout Indonesia, human resource management is important for the development and progress of the company. Along with its development, the selection of outstanding partners has so far been done manually, which is directly selected by the mentor from the partner and does not pay attention to the criteria. Therefore, we need a decision support system (DSS) in determining partners who excel by taking into account the weight of the criteria. That way it produces a clear and time-consuming calculation where the calculation begins to determine the variables used to calculate the value of errors or optimize the estimation or selection of the highest and lowest values.